Graphene-based materials and their composites: A review on production, applications and product limitations - Mohan, Velram Balaji; Lau, Kin-tak; Hui, David; Bhattacharyya, Debes (Composites. Part B, Engineering, 2018)
Recent years have perceived many innovations in research and advancement of graphene, the thinnest two-dimensional atomic material. Graphene-based materials and their composites possess promising applications in wide range of fields such as, electronics, biomedical aids, membranes, flexible wearable sensors and actuators. The latest studies and progression in this subject area often produce inconsistent or inconclusive results. This review article assesses and summarises published data so as to provide a critical and comprehensive overview of state of the art. Firstly, the distinct structural nature of the graphene materials available is elucidated, as well as different production techniques available thus far. The assessment then discusses the various composites focusing different sub-functional regimes such as mechanical and collective functional applications such as energy, electronics biomedical, membranes and sensors. The utilisation of graphene and its derivatives in the manufacture of nanocomposites with different polymer matrices has been reconnoitred. Finally, a conclusion and perspective are given to discussing the remaining challenges for graphene nanocomposites in functional science and engineering.